Synthesis of complementary hierarchical structured Si/C composites with high Si content for lithium-ion batteries - Yue, Xin-Yang; Yan, Zhong; Song, Yun; Wu, Xiao-Jing; Zhou, Yong-Ning (Nanoscale, 2018)
Si/C composites are considered as the most promising anode materials for next-generation lithium-ion batteries (LIBs) due to their high specific capacity and low cost. However, the commercialized Si/C composites cannot maintain a Si content over 10 wt% for sustaining an acceptable cycle life. To achieve long-term cycle stability for Si/C composites with high Si content is still very challenging. Here, we report a rationally designed double-morphology Si/graphene (DMSiG) composite with a high Si content of 78 wt%, and prove its feasibility as a high performance anode material for LIBs. DMSiG composes of Si quantum-dot decorated graphene and mesoporous Si spheres with a complementary hierarchical structure. The graphene framework enhances the electronic conductivity, alleviates the aggregation of mesoporous Si spheres and provides space and flexibility to buffer the volume change during cycling. Mesoporous Si spheres contribute to a large reversible capacity and support the hierarchical architecture of DMSiG. The Si quantum-dots help to build firm connections between graphene and mesoporous Si spheres to avoid their separation during cycling. Coupling these features together, the DMSiG anode delivers a high reversible capacity of 1318 mA h g −1 at a current density of 500 mA g −1 and 684 mA h g −1 at 2000 mA g −1 . A double-morphology Si/C composite with a complementary hierarchical structure is reported as a new anode material for lithium batteries.